Tuberculosis: The Interrelationship with Oral Health - Ramesh Nagarajappa1, Debasruti Naik2, Gayathri Ramesh3, Karishma Rathore4, Sthitaprajna Lenka5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
One-fourth of the population globally is infected utilizing a bacterial infection-tuberculosis (TB). TB remainsthe most contagious killer disease globally having 10 million people falling ill with TB. The transmissionroute of TB is through the air and when symptoms occur, Therefore, as a dentist we need to be aware oforal tuberculosis such that proper protocol can be followed in our daily practice. This article highlights theimportant oral manifestation of tuberculosis and its confirmed diagnostic criteria so that a dentist can followall the guidelines for proper management of a tuberculosis-infected dental patient.